2008
DOI: 10.4012/dmj.27.654
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental conditions on orthodontic bracket bonding of self-etching systems

Abstract: The influence of temperature and relative humidity (RH) on the bond strength of orthodontic adhesives was investigated. Two self-etching/composite type, one acid-etching/composite type, and one acid-etching/PMMA type of adhesives were examined under different temperature and RH conditions. Orthodontic brackets were bonded to bovine enamel, and shear bond strength test was performed at a crosshead speed of 1.0 mm/min after 24-hour storage in 37°C water. Data were analyzed by Tukey ' s HSD test. Each specimen wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Several researchers have described residual adhesive levels after debracketing, at various bond strengths (20)(21)(22)(23). Rikuta et al (24) reported that an area of more than 50% of the SB, which was used to bond the metal bracket onto the tooth surface in a shear test, occurred in 90% of specimens. Algera et al (25) reported that a remnant area of more than 50% was common.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have described residual adhesive levels after debracketing, at various bond strengths (20)(21)(22)(23). Rikuta et al (24) reported that an area of more than 50% of the SB, which was used to bond the metal bracket onto the tooth surface in a shear test, occurred in 90% of specimens. Algera et al (25) reported that a remnant area of more than 50% was common.…”
Section: Discussionmentioning
confidence: 99%
“…32 Discrepancies regarding the previously reported bond strength values might result from the different surface treatments, different modes of measurement and different operators. [33][34] Regarding the effect of saliva contamination on the enamel bond strength of self-etching adhesives, in previous studies, self-etching adhesives were usually used prior to bracket bonding [6][7][8][9][10][16][17][18][26][27] or placement of the fissure sealants [21][22][23] and they were rarely applied with salivary contamination for resin restorations. 24 In the current study, short-term contamination with saliva either before or after priming had a detrimental effect on the enamel µTBS of self-etching adhesives (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the humidity of the oral environment makes high in vitro adhesion difficult to achieve 1,6,18) . Contamination of the adhered surface by saliva or blood may also inhibit bonding 3,5,9,11,13,17) . This suggests the potential of the rubber dam isolation technique in preventing such contamination and reducing humidity 12) .…”
Section: Introductionmentioning
confidence: 99%